Extreme enhancement of the nonlinear elastic response of elastomer nanoparticulate composites via interphases. (1st January 2019) - Meddeb, Amira B.; Tighe, Tim; Ounaies, Zoubeida; Lopez-Pamies, Oscar
Abstract: Over the last two decades, it has become increasingly unarguable that the addition of a small amount of nanoparticles to elastomers can lead to a drastic enhancement of their elastic response not only at small deformations but, more importantly, at large deformations. Yet, because of the experimental difficulties of conducting direct quantitative measurements of mechanical properties at the length scale of the nanoparticles together with the mathematical challenges associated with the analysis of large deformations in the presence of nanoscale heterogeneities, the precise mechanisms responsible for such an enhancement have remained unresolved. This paper reports a combined experimental/theoretical investigation aimed at revealing and quantifying the precise mechanisms behind the enhanced elastic properties of a prototypical class of elastomer nanoparticulate composites: polydimethylsiloxane (PDMS) filled with an isotropic distribution of TiO2 nanoparticles. The synthesized composites exhibit drastically enhanced stress-stretch responses, featuring up to about a 10-fold increase with respect to the response of the unfilled PDMS elastomer, over the entire spectrum of small and large deformations considered. Inter alia, it is found that the "bulk" PDMS elastomer — i.e., the regions of the PDMS elastomer not immediately surrounding the nanoparticle aggregates formed during the synthesis process — is softer than the unfilled PDMS elastomer, while the "interphasial" PDMS elastomer surrounding the aggregates is significantly stiffer. The latter mechanism is found to rule over the former and to constitute the dominant mechanism behind the drastic enhancements in the macroscopic elastic properties of the composites. Graphical abstract: Image 1